Pengaruh Kualitas Tidur Terhadap Kejadian Kejang Pada Pasien Epilepsi - Dansen Frans Louise Draven Rudyanto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Epilepsy is the most common neurological disorder. In developing countries, the incidence of epilepsy is higher than in developed countries. The incidence of seizures in epilepsy can be reduced with regular treatment, but not a few who experience recurrent seizures, this can be influenced by several factors other than irregular treatment. One of the factors is the influence of sleep quality. Objective: To find out more about the effect of sleep quality on the incidence of seizures in epilepsy. Methods: Using literature studies from several national and international journals. Conclusion: There is an effect of sleep quality on the incidence of seizures in epileptic patients.